Theoretical consideration of inherent monitoring of educational system of Germany - Inna Shymkiv (Vasyl Stefanyk Precarpathian National University, 2017)
The article deals with the basic nature, principles and forms of organization of inherentmonitoring of educational system of Germany. The methods of inherent monitoring have beenanalyzed. The content of the programmed of monitoring has been defined. The importance ofthe reception of the productive tendencies of the foreign ways of organization of inherentmonitoring in the context of rapprochement and mutual enrichment of national educationalsystems has been concluded. Key words: inherent monitoring, methods of inherent monitoring, appraisal, quality ofeducation.